The Routledge handbook of motherhood on screen
1 online resource (xvii, 488 pages)
Keywords: "The Routledge Handbook of Motherhood on Screen offers a comprehensive global analysis of the representation of Mothers and Motherhood in contemporary screen industries and online spaces. Over five distinct sections, this handbook examines how the complexities and realities of contemporary motherhood are translated to the screen. Offering a full scholarly overview of the field, this handbook provides a ground-breaking and important contribution to our understanding of motherhood on screen. The geographical and genre reach of the handbook presents new ways of theorising and reframing current scholarly debate, and gives a wide-ranging and comprehensive contribution to knowledge of on-screen representations. An international team of established scholars and emerging voices provide analysis of representations from around the world, spanning a breadth of genres. The chapters situate transnational screen representations of motherhood in the 21st Century and assess the implications of contemporary representation of motherhood. Thoroughly challenging and expanding understandings of motherhood and mothers, this handbook will be an essential multi-faceted publication for researchers and students of film, TV, animation, motherhood, gender studies, feminism, ageing studies, anthropology and sociology"--